Metacognitive strategy training and teacher attitude and performance - Avila, Ronita M.; Baetiong, Lourdes R. (2012)
This study aimed to determine the effects of an in-service training on the metacognitive strategies of public secondary teachers in English in the District of Talacogon, Agusan del Sur, CARAGA Region XIII. Specifically, it sought to answer the questions: (1) What is the teachers' attitude towards the use of metacognitive strategies before and after the in-service training on metacognitive strategies? and (2) Is there a significant difference between the participants' teaching performance before and after the in-service training on metacognitive strategies? A two-day in-service training on metacognitive strategies for sixteen (16) English teacher-participants was developed and implemented. Using the instruments, Teachers Attitude Scale towards Metacognitive Strategies, and the Observation Checklist on the Use of Metacognitive Strategies, the study yielded results indicating that the in-service training on metacognitive strategies significantly affected the teacher-participants' attitude towards the use of metacognitive strategies and their performance in teaching Reading.
Keywords: Metacognition; In-service training of teachers